2018
DOI: 10.1017/s0022029918000687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pasteurization and storage conditions on donkey milk nutritional and hygienic characteristics

Abstract: Until now there are only few data on the effects of thermal treatments on the nutritional and hygienic characteristics of donkey milk. This Research Communication aims to provide information on the effects of pasteurization (at +65 °C for 30 min) and prolonged storage at refrigeration and freezing temperatures (21 d at + 3 °C ± 2 °C and up to 90 d at -20 °C ± 5 °C) on some nutritional and hygienic characteristics of Amiata donkey milk. The milk was monitored by chemical and microbiological analysis. Pasteuriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The effectiveness of in-vat pasteurization at +65 °C for 30 min and storage at refrigeration (+3 °C ± 2 °C) and freezing temperatures (−20 °C ± 5 °C) on some hygienic characteristics of donkey milk was investigated. The treatment ensured compliance with EC Regulation No 1441/2007, as Enterobacteriaceae were never found in the milk, and TBC at 30° never went beyond 1 log cfu ml (initial load was 4.84 log cfu mL −1 ) [ 55 ]. A study on 101 half-udder milk samples showed very low values of TBC (<250 cfu/mL) and a minor presence of pathogens: Staphilococcus aureus was isolated from only five milk samples (three animals), Streptococcus equi from two samples, and Streptococcus equisimilis from a single sample.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…The effectiveness of in-vat pasteurization at +65 °C for 30 min and storage at refrigeration (+3 °C ± 2 °C) and freezing temperatures (−20 °C ± 5 °C) on some hygienic characteristics of donkey milk was investigated. The treatment ensured compliance with EC Regulation No 1441/2007, as Enterobacteriaceae were never found in the milk, and TBC at 30° never went beyond 1 log cfu ml (initial load was 4.84 log cfu mL −1 ) [ 55 ]. A study on 101 half-udder milk samples showed very low values of TBC (<250 cfu/mL) and a minor presence of pathogens: Staphilococcus aureus was isolated from only five milk samples (three animals), Streptococcus equi from two samples, and Streptococcus equisimilis from a single sample.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…However, very recently, scientific research has shown its value and importance in many fields. Several studies support the idea that donkey milk could be helpful for babies and patients suffering from cow’s milk protein allergy (Martini, Salari, et al., 2018), and play a significant role in improving the health of certain healthy individuals (e.g., elderly people, some subhealthy people with dyslipidemia and obesity) as well in individuals with a certain disease (e.g., fatty liver, diabetes, and IBD). In the past, the consumption of donkey milk was mainly due to the higher abundance of vitamin B and vitamin C. With the development of technology, especially omics, more bioactive and antimicrobial properties of donkey milk (such as proteins and bioactive peptides) were observed (Aspri et al., 2018; Brumini et al., 2016; Cunsolo et al., 2017).…”
Section: Donkey Milk Nutritional Composition and Valuementioning
confidence: 88%
“…Coagulase-positive staphylococci were found in the raw donkey milk, with an average count of 1.7 × 10 2 cfu/ml [13].…”
Section: Microbiological Hazardsmentioning
confidence: 99%
“…The raw milk for human consumption can be sold directly at farms; it is also pasteurized (rarely, UHT-treated or freeze-dried), packed, and sold in shops, pharmacies, or it is sold online [12]. It is not always or easily available on the market and domestic milk freezing of donkey milk is a common practice [13].…”
Section: Introductionmentioning
confidence: 99%